MBD2 mediates Th17 cell differentiation by regulating MINK1 in Th17-dominant asthma - Chen, Zhifeng; Shang, Yulin; Yuan, Yu; He, Yi; Wasti, Binaya; Duan, Wentao; Ouyang, Ruoyun; Jia, Jingsi; Xiao, Bing; Zhang, Dongshan; Zhang, Xiufeng; Li, Jianmin; et al. (Frontiers in Genetics, 2022)
Objective Asthma is a highly heterogeneous disease, and T-helper cell type 17 (Th17) cells play a pathogenic role in the development of non-T2 severe asthma. Misshapen like kinase 1 (MINK1) is involved in the regulation of Th17 cell differentiation, but its effect on severe asthma remains unclear. Our previous studies showed that methyl-CpG binding domain protein 2 (MBD2) expression was significantly increased in patients with Th17 severe asthma and could regulate Th17 cell differentiation. The aim of this study was to investigate how MBD2 interacts with MINK1 to regulate Th17 cell differentiation in Th17-dominant severe asthma. Materials and methods Female C57BL/6 mice and bronchial epithelial cells (BECs) were used to establish Th17-dominant severe asthma mouse and cell models. Flow cytometry was used to detect Th17 cell differentiation. Western blot was used to detect MBD2 and MINK1 expression. To investigate the role of MBD2 and MINK1 in Th17 cell differentiation in Th17-dominant severe asthma, MBD2 and MINK1 genes were silenced or overexpressed by small interfering RNA and plasmid transfection. Results The mouse and BECs model of Th17-dominant severe asthma were established successfully. The main manifestations were increased neutrophils in BALF, airway hyperresponsiveness (AHR), and activated Th17 cell differentiation. The expression of MBD2 in lung tissues and BECs from the Th17-dominant severe asthma group was significantly increased, while the corresponding expression of MINK1 was significantly impaired. Through overexpression or silencing of MBD2 and MINK1 genes, we have concluded that MBD2 and MINK1 regulate Th17 cell differentiation. Interestingly, MBD2 was also found to negatively regulate the expression of MINK1. Conclusions Our findings have revealed new roles for MBD2 and MINK1, and provide new insights into epigenetic regulation of Th17-dominant severe asthma, which is dominated by neutrophils and Th17 cells. This study could lead to new therapeutic targets for patients with severe asthma.